Pengaruh Kualitas Layanan, Citra Merek Dan Harga Terhadap Kepuasan Pengguna Layanan Internet PT. Telkomsel di Kota Bengkulu - Yoko Diotiharta; Ali Muktiyanto; Iqbal Miftakhul Mujtahid (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The objective of this research is to analyze the effect of service quality, brand image and price of customer satisfaction internet service PT. Telkomsel in Bengkulu City. This study is a quantitative descriptive which is focus the on issues such as the current facts of a particular phenomenon by using the statistic calculations. The type of data used a primary data that is collected from questionnaires. Respondents of this study is the community of Bengkulu city, which uses internet service PT. Telkomsel as many 115 students were taken with the accidental sampling technique. The methods of data analysis used are descriptive analysis by using the mean, frequency distribution table and multiple linear regression analysis. Based on the analysis, the result that partial service quality and brand image positive and significant influence on customer satisfaction with internet services PT Telkomsel in Bengkulu city, while the price of negative and significant effect on customer satisfaction internet service PT. Telkomsel in Bengkulu City. And simultaneously service quality, brand image and price significantly influence customer satisfaction internet service PT. Telkomsel in Bengkulu City